Online Public Health Nurse-Delivered Group Cognitive Behavioral Therapy for Postpartum Depression: A Randomized Controlled Trial During the COVID-19 Pandemic - Huh, Kathryn; Layton, Haley; Savoy, Calan D; Ferro, Mark A; Bieling, Peter J; Hicks, Amanda; Van Lieshout, Ryan J (The journal of clinical psychiatry, 2023)
Rates of postpartum depression (PPD) increased during the COVID-19 pandemic, further highlighting the need for effective, accessible treatments for PPD. While public health nurses (PHNs) can be trained to help treat PPD, it is not known if they can effectively deliver evidence-based psychotherapies online to those with PPD. Mothers (n = 159) living in Ontario, Canada, with an Edinburgh Postnatal Depression Scale (EPDS) score ≥ 10 and an infant < 12 months of age were randomized to receive a 9-week group cognitive behavioral therapy (CBT) intervention delivered by PHNs over Zoom, between October 2020 and November 2021. Experimental group participants received CBT plus treatment as usual (TAU), and control participants received TAU alone. Participants were assessed at baseline (T1), 9 weeks later (T2), and 6 months after T2 (T3). Primary outcomes were changes in EPDS score and current major depressive disorder (MDD) as measured by the Mini International Neuropsychiatric Interview. Secondary outcomes included worry, social support, the mother-infant relationship, and infant temperament. At T2, experimental group participants showed clinically and statistically significant reductions on the EPDS ( = 0.65) and decreases in postpartum worry ( = 0.38) and rejection and pathological anger toward their infant ( = 0.44). They were also less likely to meet diagnostic criteria for current MDD compared to control participants (OR = 5.09; 95% CI, 1.18-21.98; number needed to treat [NNT: 3.7]). These improvements remained stable 6 months later (T3). PHNs can be trained to deliver effective online group CBT for PPD to reduce depression and worry and improve aspects of the mother-infant relationship, and they represent an important way to increase access to effective treatment for PPD. ClinicalTrials.gov identifier: NCT04928742.